PURIFIED GAMBIR (UNCARIA GAMBIR (HUNTER) ROXB.) ATTENUATE RENAL FUNCTION IN ALLOXAN-INDUCED DIABETIC MALE RATS - RACHMAINI, FITRI; ARMENIA; ABDILLAH, RAHMAD (International Journal of Applied Pharmaceutics, 2024)
Objective: Diabetes and its vascular complications could prevent by antioxidants. Purified gambir is the purified extract of Uncaria gambir (Hunter) Roxb, which contains more than 90% catechins and scientifically work as antioxidant. This study aimed to determine the effect of purified gambir on renal function in alloxan-induced diabetic Wistar Kyoto rats. Methods: Diabetic rats were induced by alloxan 125 mg/kgBW by intraperitoneal injection. Forty-five diabetic rats were divided into five groups, diabetic control group treated with vehicle, a positive control group treated with glibenclamide at dose 0.45 mg/kgBW, and treatment groups of purified gambir at doses of 2.50, 5, and 10 mg/kgBW for 14 d. Blood glucose, water intake, urine volume, creatinine clearance, renal ratio, and urine density were measured on day 3, 7, and 14. All data were analyzed by two-way ANOVA followed by Duncan Multiple Range Test. Results: Purified gambir significantly lower blood glucose (p<0.05) and had a significant effect (p<0.05) on renal function parameters in diabetic rats. Duration of treatment purified gambir in diabetic rats had a significant effect (p<0.05) on water intake, urine volume, creatinine clearance and renal ratio. Conclusion: This result show that purified gambir at dose 2.5 mg/kgBW increased the renal function of diabetic rats, in contrast, purified gambir at dose 5 and 10 mg/kgBW attenuate renal function of diabetic rats